ANALISIS HOTSPOT STRESS PADA SAMBUNGAN TUBULAR BRACE T DENGAN SIMULASI PEMBEBANAN TARIK PADA STRUKTUR BANGUNAN LEPAS PANTAI TIPE JACKET PLATFORM. - Rudi Siswanto; Anwar (Jurnal Poli-Teknologi, 2023)
Abstract The jacket platform type offshore building structure is a building that is often used for oil and gas exploitation activities, environmental loads such as wave loads that occur continuously can cause the offshore building structure to experience fatigue. Tubular joints are areas that often experience fatigue or cracking due to stress concentrations that occur in the tubular joints. This research was conducted to find out and calculate the greatest stress points that occur in tubular joints for the T-brace model. The results showed that the hotspot stresses occurred in the elements in the welding area of the joints with a working stress value of 1577.3 Mpa and a value for calculating N integration of 12704.87. Keywords: Hotspot Stress, Tubular Joint, T Brace